2015
DOI: 10.1108/ijrdm-07-2012-0061
|View full text |Cite
|
Sign up to set email alerts
|

Consumer confusion in German food retailing: the moderating role of trust

Abstract: Purpose – Due to the rising number of product, service, and shopping possibilities available to consumers, food shopping has become increasingly more complex. As a result, consumers can become confused, and this state of confusion may influence their purchase behaviour (e.g. may cause them to not buy a product) and the personal needs they have in a shopping environment (e.g. certification to signal product quality, salesperson consultation for assistance in decision making, or governmental regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 83 publications
0
33
0
Order By: Relevance
“…The results of their research state that there is a relationship between promotion of buying decisions. The other researchers, such as Wobker et al (2015), also confirm that there is a relationship between promotion and buying decision. Then, the researcher concluded that there is a relationship between promotion and buying decision.…”
Section: Promotion On Buying Decisionmentioning
confidence: 68%
See 4 more Smart Citations
“…The results of their research state that there is a relationship between promotion of buying decisions. The other researchers, such as Wobker et al (2015), also confirm that there is a relationship between promotion and buying decision. Then, the researcher concluded that there is a relationship between promotion and buying decision.…”
Section: Promotion On Buying Decisionmentioning
confidence: 68%
“…This result can also be interpreted that any promotional enhancement will increase consumer's buying decision of processed peanut food products in Central Java. Blattberg et al (1995) and Wobker et al (2015) state that promotion is a marketing activity that seeks to disseminate information, to influence and remind target markets of the company and its products to be willing to accept, buy and be loyal to the products offered by the company. This study supports the previous studies conducted by Huang and Yang (2015) and Wobker et al (2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations